PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBASIS KAHOOT TERHADAP KEAKTIFAN BELAJAR SISWA di SMP NEGERI 1 TURI - Aprillia, Annisaa' Fitri; Cholifah, Nur (Universitas Tanjungpura, 2025)
Abstract Traditional teaching methods often strunggle to maintain student interest, particularly in Social Studies (IPS), where passive learning can lead to disengagement. This research investigates the impact of the Kahoot integrated Teams Games Tournament (TGT) model on the learning engagement of eight-grade students at SMPN 1 Turi. Employing a quantitative approach with a quasi experimental design, data were collected through surveys and classroom observations. The findings reveal that the TGT model significantly enhanced students engagement, with a 15% increase observed in the experimental group and a notably higher N-Gain score compared to the control group. The implementation of this model fostered active participation, peer collaboration, and a healthy sense of competition among students. These results suggest that integrating Kahoot into the Teams Games Tournament model offers a promising strategy for improving student involvement and elevating the overall quality of Social studies learning.